'Because it's fun': English and American girls' counter-hegemonic stories of alcohol and marijuana use. (26th November 2019) - Arnull, Elaine; Ryder, Judith
ABSTRACT: Girls' alcohol and other drug (AOD) use are depicted culturally as problematic. In this comparative, qualitative, study the voices of 59 English and American justice-involved girls give a counter-hegemonic portrayal of their alcohol and marijuana use. In their stories, we see how their AOD use is pleasurable and boundaried. AOD use involves negotiated risk within the situated context of shared experience and friendship networks that heighten and promote pleasure and fun. The findings offer the opportunity to address the 'credibility gap' in international health promotion policy. Our aim is to promote the adoption of policy approaches that recognize the complexity of girls' lives and draw on strategies they have devised.